2019
DOI: 10.1044/2018_jslhr-l-18-0071
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-Based Word Learning in Young Typically Developing Children and Children With Development Language Disorder II: A Comparison of Retrieval Schedules

Abstract: Purpose Retrieval practice has been found to be a powerful strategy to enhance long-term retention of new information; however, the utility of retrieval practice when teaching young children new words is largely unknown, and even less is known for young children with language impairments. The current study examined the effect of 2 different retrieval schedules on word learning at both the behavioral and neural levels. Method Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
85
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 67 publications
11
85
2
Order By: Relevance
“…Another parallel finding pertains to time; in both studies, children with DLD retained the words over 1 week as successfully as their TD peers. Similar findings were seen for our study comparing spaced retrieval with immediate retrieval (Haebig et al, 2019) and earlier studies of young adults by McGregor et al (2017) that used a different learning procedure. From these findings, we cannot conclude that individuals with DLD function adequately in their longterm retention.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another parallel finding pertains to time; in both studies, children with DLD retained the words over 1 week as successfully as their TD peers. Similar findings were seen for our study comparing spaced retrieval with immediate retrieval (Haebig et al, 2019) and earlier studies of young adults by McGregor et al (2017) that used a different learning procedure. From these findings, we cannot conclude that individuals with DLD function adequately in their longterm retention.…”
Section: Discussionsupporting
confidence: 90%
“…However, to argue that the benefits of the RRCR condition were attributable in part to spaced retrieval rather than to the opportunity for retrieval more generally, we can only resort to our previous findings. In a study of novel noun learning, Haebig et al (2019) found that a spaced retrieval condition produced greater recall than a condition that provided the same number of retrieval opportunities but with no intervening items. With such immediate retrieval, the context changes very little, and hence, the context representation does not become more distinctive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for 'little and often', if embedded within longer sessions with mixed goals, may be confounded by an increase in variability and intervention context. By changing the target after two minutes, both variability and context change, both of which are thought to be advantageous to children's language learning, (Haebig et al, 2019;Plante et al, 2014). What is unclear is how many times (or if at all) the target was revisited within a single session, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although results suggest no spaced learning advantage between sessions (for morphosyntax) if all other dosage characteristics are controlled, inconsistencies in the definitions of spaced/distributed and massed/concentrated have been problematic, making cross-study comparison and clinical application difficult. Within session spacing has been under-researched and while Plante and colleagues (2019) report no differences in treatment effects based on the within session density with which the dose was given, changes in dose form context which inadvertently create within session spacing have been found to be advantageous (Haebig et al, 2019). Finally, frequent interventions (2/3 times per week) that target language goals for short periods, or less frequent interventions (1 per week or fortnight) targeting language goals for longer, have been found to yield the best outcomes in relation to composite language measures.…”
Section: Summary and Recommendations For The Futurementioning
confidence: 99%